Effects of monosaccharide composition on quantitative analysis of total sugar content by phenol-sulfuric acid method - Yue, Fangfang; Zhang, Jinrui; Xu, Jiaxin; Niu, Tengfei; Lü, Xin; Liu, Manshun (Frontiers in Nutrition, 2022)
Phenol-sulfuric acid method is one of the most common methods applied to the analysis of total sugar content during polysaccharides study. However, it was found that the results obtained from the phenol-sulfuric acid method was generally lower than the real total sugar content, especially when acidic monosaccharides were contained in the polysaccharides samples. Therefore, the present study focused to unveil the proposed problem. Based on the optimization of colorimetric conditions, such as optimal wave length of absorption, linearity range, color reaction time and temperature, it indicated that the phenol-sulfuric acid method was a convenient and accurate way for the total sugar content analysis. In addition, the color-rendering capabilities of 10 common monosaccharides were systematically analyzed to obtain a relative correction factor for each monosaccharide relative to glucose, which was proved to be the main reason for the deviation in the detection of total sugar content. Moreover, the key points during the application of phenol-sulfuric acid method were suggested. This study provides a scientific theoretical basis and a reliable experimental research method for the accurate determination of total sugar content by the phenol-sulfuric acid method, and which will also promote the application of this convenient method in the polysaccharides study.